INFLUENCE OF THE MOISTURE CONTENT OF FROZEN LOGS ON ENERGY REQUIRED FOR THEIR DEFROSTING IN BOILING PITS - Deliiski, Nencho; Dzurenda, Ladislav; Angelski, Dimitar; Vitchev, Pavlin; Atanasova, Krasimira (Innovation in Woodworking Industry and Engineering design, 2024)
With the help of our own non-stationary model, the temperature field and defrosting durations of frozen beech logs with a diameter of 0.4 m, initial temperature of −10 oC, and moisture content of 0.4 kg∙kg-1, 0.6 kg∙kg-1, and 0.8 kg∙kg-1 were determined at water temperatures in the boiling pit equal to 80oC. Using the determined durations, the change in energy required for carrying out of the entire defrosting process and that for each of the 5 components of the pit’s thermal balance was calculated. Computer simulations were performed for a well-insulated concrete pit with working volume of 20 m3 and degree of filling with logs f equal to 25%, 50%, and 75%. It was found that at maximum possible value f = 75% the total energy consumption of the pit increases from 145.1 kWh.m-3 to 180.2 kWh∙m-3, i.e. by 24.2% when the moisture content of the frozen logs increases from 0.4 kg∙kg-1 to 0.8 kg∙kg-1. With a decrease in f, the thermal efficiency of the pit decreases almost proportional to f, mainly due to the increase in the specific energy required to heat the water in the pit.